Novel approaches for combating bovine respiratory disease - Flippin, Emma Kathryn (Kansas State University, 2023)
Bovine respiratory disease (BRD) is the leading cause of illness and death in cattle throughout North America, costing producers $800 to $900 million each year. Over the past 30 years, there has been extensive research conducted to study BRD, but few advances have been made to reduce the negative effects of the disease. The significant impact of BRD on the cattle industry creates opportunities for new and novel approaches for combating the disease to be explored and researched. The objective of this paper is to provide an overview of current BRD understanding and traditional approaches for treating and preventing the disease. Additionally, this paper will provide a discussion on novel approaches to mitigate risk of BRD by understanding the impact of animal genetics, and managing environmental and animal social factors. Bovine respiratory disease is classified as a multifactorial, complex disease caused by both bacterial and viral pathogens. Major risk factors for development of BRD include: presence of disease-causing infectious agents, host factors that increase susceptibility of animal, and external environmental factors. Scenarios when all risk factors are present indicate ideal environments for BRD-causing pathogens to infect cattle. High stress environments post transport, post weaning, or any activity that requires movement of animal from its pen (i.e. vaccination, treatment, sorting pens, etc.) often create the described ideal environment. Identification of risk factors associated with BRD is an important step in preventing and managing disease. Prevention can also be obtained through early vaccination protocols, biosecurity, metaphylaxis and other animal management practices. In the US, over 90% of large feedlots reports BRD as the most frequent disease resulting in increased medication costs and death. Nearly 20% of beef cattle in the United States will require clinical treatment of BRD at some point in their lives. Clinical signs can include nasal discharge, lethargy, inappetence, coughing and labored breathing. Early detection of clinical signs is crucial in treating and preventing the spread of disease. A diagnosis of BRD in cattle is made using clinical signs, history, and/or laboratory testing. Treatment practices include antimicrobial therapy, but with increasing public concern regarding antimicrobial use in cattle, novel approaches to combating the disease are needed. Novel approaches to combat BRD include understanding the importance of genetics and genomics when selecting cattle, implementing new protocols to circumvent environmental risk factors, and by providing disease preventative animal management and biosecurity practices at each stage of production.
Keywords: Bovine respiratory disease; Cattle; BRD